MATRIX OF DEPENDENCE, POSTCOLONIALISM, AND SOCIAL MEDIA REGULATION IN AN AFRICAN CONTEXT - Obia, Vincent Adakole (AoIR Selected Papers of Internet Research, 2023)
This paper considers the relation of dependence that defines the practice of social media and internet content regulation in an African context. With social media regulation in Nigeria as a case study, it gives attention to debates drawn from postcolonial thinking, structural imperialism, and platform power, presenting new research on the concept of the matrix of dependence. To do this, I gather data by interviewing 19 stakeholders on what they perceive as credible alternatives to social media regulation in Nigeria, given their opposition to the proposed formal approach represented by the 2019 Internet Falsehood Bill. Analysis was done using Braun and Clarke’s (2021) reflexive thematic analysis. Findings point to four alternatives/themes: copying Western nations, platform self-regulation, governance built on trust, and digital media literacy. I expand on these findings to show that underlying each suggested alternative is the notion of subalternity under which Nigeria functions as it pertains to new media governance. I further argue that this construct can be applied to the wider African continent, suggesting that postcolonialism shapes the use and regulation of new media technologies in what can be understood as the matrix of dependence.